Abrasion Resistance of Gabion Wires Against Simulated Weathering and Field Conditions - K.Tan, K.; M. Chan, C.; Liew, A. (International Journal of Engineering and Technology, 2019)
Gabions are steel wire mesh cages filled with stones of appropriate size and mechanical characteristics. It is widely applied in geotechnical and hydraulic engineering as retaining and erosion control structures. Therefore, it must be made of durable materials to withstand most of the site conditions and weathering. Various coating technologies has been applied to enhance the lifespan. This study was conducted to examine the effect of moisture, acid, alkaline and saltwater under ultraviolet radiation and heat on the durability of a plastic-based coating material used as protective coating of gabion wires. Exposure conditions were simulated via natural weathering method, where they were placed outdoors at a designated test station. The samples were soaked and covered in soil to represent applications in waterlogged as well as buried / semi-buried field conditions. The weathered samples were subjected to the abrasion test after different periods of exposure over 250, 500 and 750 hours. 3 samples each were tested to maintain consistency in the measurements taken. Degradation of the coating material due to the simulated weathering conditions varied in terms of rate and severity, though the overall results indicate alkalinity to be more detrimental than acidity and salinity. Variation among the samplesâ€™ degradation was observed to be more distinct in the terms of soaked and soil-covered conditions. In conclusion, samples buried in alkali-tainted soil are the least durable against abrasion as the recorded mass loss percentage was the highest, followed by acid-soaked samples. Some plausible explanations include the lack of heat built up on seawater-soaked samples leading to less degradation, and surfacial biofouling of soaked samples serving as a protection against UV light or chemical attack. Further work is in the pipeline to examine the effects of longer exposure period and wider range of exposure conditions to verify the coating materialâ€™s long-term performance.Â Â